Effects of Morinda citrifolia L. leaf aqueous extract on fatigue and bone health - Mohamad Shalan, Nor Aijratul Asikin (2015)
Morinda citrifolia, locally known as Mengkudu, has been used for thousands of years in folk medicine. Traditionally, M. citrifolia fruit has been consumed to combat fatigue and help restore vigor to the body while its leaf crude extract has been used for patients with bone fractures or dislocation. Yet, the explorasion is too little to understand the cellular mechanisms behind these effects. Therefore, we aimed to evaluate the anti-fatigue and bone protective potential beneficial effects of M. citrifolia using in vivo model. Since the rising numbers of hepatotoxicity case reports on M. citrifolia fruit, a chronic toxicity study was conducted in vivo, using both M. citrifolia fruit and leaf aqueous extract. The six months study showed the M. citrifolia fruit extract at a dose of 2 mg /ml drinking aqueous, produced chronic toxicity effects apparent through deteriorated liver histological observations (hepatocyte necrosis), reduced liver length, serum ALP and albumin reduction, injury symptoms (hypoactivity, excessive grooming, sunken eyes and hunched posture) and 8% mortality within three months. This hepatotoxicity observations support the six liver injury reports in humans which was linked to M. citrifolia fruit juice consumption. However both doses of M. citrifolia leaf extracts and the low dose of fruit extract (1mg/ml drinking aqueous) demonstrated no detectable toxicity. Exercised-induced fatigue was used to examine the ergogenic effects of M. citrifolia leaf aqueous extract. The four weeks study repeatedly showed the M. citrifolia leaf extract (containing 6 mg/g scopoletin) progressively prolonged the time to exhaustion by three-fold longer than the group of control and tea extract. The M. citrifolia leaf extract improved antioxidant activities, regulated stress hormone and neurotransmitters expressions, enhanced fatty acid metabolism and mitochondrial biogenesis, augmented skeletal muscle angiogenesis and increased the anti-inflammatory responses.Bone protective ability of M. citrifolia leaf aqueous extract was evaluated using ovariectomy-induced osteoporosis model. The four months study showed the M. citrifolia leaf extract dose-dependently favours bone regeneration and suppressed bone resorption through improving the bone size and structure, bone mechanical properties (strength and flexibility), and bone mineralization and density. As was suggested from gene expression study outcomes, M. citrifolia leaf bone protective mechanisms might involved the enhancement of bone formation cells generation and survival, and inhibition of bone resorption cells growth and activities. The expression of estrogen receptor marker also suggests that bone loss prevention by M. citrifolia might be due to phytoestrogenic activities. It can be concluded from this study that the consumption of M. citrifolia leaf will not lead to hepatotoxicity, however the hepatotoxicity effects of the M. citrifolia fruit extract (at 2mg/ml dose) may be caused by the anthraquinones present in the seeds and skin. The M. citrifolia leaf extract helped delay fatigue by enhancing energy production, regulation and efficiency, which suggests benefits for physical activities and disease recovery. M. citrifolia leaf extract also protected bone from deterioration under condition of estrogen deficiency, indicating benefits for the aged and menopausal women.